1220 Developing facilitator training toolkits by intercountry networking for adjusting participatory steps of preventing overworking to local situations. (24th April 2018) - Kogi, K; Sano, Y; Nakao, T; Yoshikawa, T; Yoshikawa, E; Lee, MS; Roh, JH; Park, JS; Woo, KH
Abstract : Introduction: Awareness is growing of the need to effectively promote participatory workplace improvement in different work settings. Newly advancing networked collaboration among occupational health teams in Japan, Korea and other countries in Asia indicate the importance of relying on facilitator training in adjusting participatory programmes to each local situation. It is useful to elucidate effective ways to train facilitators acting in the local context of implementing readily feasible improvements preventing overworking in varied local situations. Methods: Commonly effective procedures for training facilitators acting in participatory action-oriented programmes for preventing overworked situations were reviewed. How the intercountry networking of these experiences contributed to the development of locally adjusted training methods was examined. Attention was paid to simplified procedures and action checklists in training facilitators supporting workers in conducting practical improvements in the local context. Results: The intercountry networking led to annual workshops that confirmed the efficacy of simplified procedures for participatory programmes aimed at locally feasible improvements. These simple procedures proved useful for achieving multifaceted improvements in work methods, physical environment and work organisation. The collaboration of network partners verified the suitability of simple procedures addressing multiple aspects of work. Reflecting this progress, the network partners developed a similarly simple process of facilitator training. The use of a locally adjusted participatory toolkit comprising illustrated good practices and an action checklist of low-cost ideas was consistent. Facilitator training utilising this toolkit in guiding workers thus proved effective in different occupations. Conclusions: Inter-country collaboration in joint development of facilitator training methods in participatory workplace improvement programmes for preventing overworking proved effective. Simplified training procedures were confirmed useful when they emphasised local good practices and facilitation by means of a locally adjusted toolkit. It is recommended to make full use of interactive networking incorporating these training features.